1971
DOI: 10.1038/icb.1971.48
|View full text |Cite
|
Sign up to set email alerts
|

Copper Deficiency in the Rat. Effect on Adenine Nucleotide Metabolism

Abstract: Summary. Copper deficiency does not influence the synthesis of ATP by liver mitochondria noc does it alter the concentration of ATP in whole liver homogenates or in isolated mitochondria, microsomes jmd supernatant. However, copper deficiency considerably reduces the affinity of mitochondria to biad adenine nucleotides on membrane preparations. This defect leads to failure of ATP transport across the inner membrane resulting in abnormal accumulation of ATP within rliitochondria incubated in vitro and a require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…It is, however, more likely that defective cytochrome oxidase activity in the brain is responsible for much of the cerebral pathology, in particular the cerebellar lesion and the myelin pallor noted in all cases. This would be in accord with the findings of Gallagher and Reeve (1971) of deficient phospholipid synthesis in the brains of copper-deficient rats.…”
supporting
confidence: 90%
“…It is, however, more likely that defective cytochrome oxidase activity in the brain is responsible for much of the cerebral pathology, in particular the cerebellar lesion and the myelin pallor noted in all cases. This would be in accord with the findings of Gallagher and Reeve (1971) of deficient phospholipid synthesis in the brains of copper-deficient rats.…”
supporting
confidence: 90%
“…This degree of involvement could be explained by deficiency of a trace element which plays a r81e in a basic enzymic process, and several studies point to such a conclusion. Gallagher and Reeve (1971) found that phospholipid synthesis is defective in the brains of copper-deficient rats. French et a/.…”
Section: Discussionmentioning
confidence: 99%
“…However, a relationship between reduced cytochrome-c oxidase activity and defective energy metabolism in causing the pathophysiological consequences associated with copper deficiency has not been clearly established. For instance, a 70%-90% reduction in cytochrome-c oxidase activity during copper deficiency either has no effect or only modestly lowers brain, liver, and platelet ATP content (5)(6)(7)(8)(9). Thus, if reduced cytochrome-c oxidase activity contributes to the biological consequences of copper deficiency, then an alternative to impaired energy production as a mechanism needs to be found.…”
mentioning
confidence: 99%